Kinematics of marathon running tactics - Erdmann, W. S.; Lipinska, P. (Human Movement Science, 2013)
We examined eight important world marathon runs including four of Haile Gebrselassie. The wrong running tactics can lead to exhaustion by the end of a run or failure in an aim of winning a race. Only a few first runners from the first 50 at the finish line ran the second part of a marathon faster than the first part. They had smaller deviations of velocity. Male and female runners differ in tactics.